When Does Work Interfere With Teachers’ Private Life? An Application of the Job Demands-Resources Model - De Carlo, Alessandro; Girardi, Damiano; Falco, Alessandra; Dal Corso, Laura; Di Sipio, Annamaria (Frontiers in Psychology, 2019)
The purpose of this study is to examine the relationship between contextual work-related factors on the one hand, in terms of job demands (i.e., risk factors) and job resources (i.e., protective factors), and work-family conflict in teachers on the other. Building on the Job Demands-Resources (JD-R) model, we hypothesized that job demands, namely qualitative and quantitative workload, are positively associated with work-family conflict in teachers. Moreover, in line with the buffer hypothesis of the JD-R, we expected job resources, in terms of support from supervisor, job autonomy, and participation in decision making, to affect this association, which is expected to be stronger when job resources are low. The study was conducted in an Italian secondary school. Overall, 122 teachers completed a self-report questionnaire aimed at determining work-family conflict, as well as job demands and resources. The hypothesized relationships were tested using moderated multiple regression. The results of this study largely support our predictions. First, both aspects of workload were positively associated with work-family conflict. Secondly, job resources, including support from supervisor and participation in decision making, buffered this association, which was stronger when resources were low. On the contrary, job autonomy did not buffer the association between workload and work-family conflict. Overall, the results of this study are consistent with the Job Demands-Resources model and contribute to to the understanding of work–family conflict among teachers. More specifically, our study suggests that teachers with high levels of job resources, namely support from supervisor and participation in decision making, can effectively cope with job demands, in terms of both qualitative and quantitative workload, thus preventing negative consequences such as conflict between work and family domains. Interventions aimed at preventing work-family conflict among teachers should encourage organizations to optimize the balance between job demands and resources, as well as the identification and training of the workers at risk of work-family conflict.